مفهوم التعرض The concept of exposure - Bader Nasser Hussain بدر ناصر حسين (Journal Of Babylon Center For Humanities Studies, 2013)
The term exposure in the Arabic language is the "View" ((meaning linguistically showed thing and I see him)), while in the Latin language meaning word exposure ((Statement of thing by reading and writing through the presentation of an orderly and convincing ideas)) (), but the concept of exposure media in the Glossary media (it is what comes out of the individual from an oral presentation or written to facts or facts) (), may be to offer a clear or implied or obscure, or it process and access information from media sources to the masses or individuals directly or indirectly (), means the media exposure is a public exposure to those means and influenced by, this effect may be consciously there of shall be intentional or unintentional and individuals each different from the others because of their differences in the extent of exposure to the media ().